Knowledge of pediatricians working in emergency sector about anaphylaxis treatment - Faria, João Carlos Pina (2018)
Introduction: Anaphylaxis is a severe, acute and potentially fatal systemic reaction. It presents several triggers and different mechanisms, however, the acute treatment is the same in all the cases. Objective: To evaluate the knowledge about treatment of anaphylaxis and anaphylactic shock (AS) of pediatricians who works in the pediatric emergency sector. Methods: Cross-sectional study through the use of a multiplechoice questionnaire with 10 questions about the treatment of anaphylaxis and AS. All the emergency room pediatricians of a general pediatric hospital were invited. Results: Fifty of fifty-ne pediatricians agreed to take part of the study. The mean of right answers was 6.32 and median of 7 (minimum 2 and maximum 10). There was an appropriate recognition about the drug of choice to initiate the treatment of anaphylaxis and AS in 96% and 92%, respectively. On the route of adrenaline administration, the adequacy of the answers was 64%. Regarding to adrenaline dose 70% were right, however the recognition of the maximum dose was 44%. When asked about the interval to repeat the adrenaline, 38% responded correctly. About adjuvant therapies to treat AS the score was 74% and 60% when questioned about the drug that prevents biphasic anaphylactic reaction. In relation to the observation time, 54% answered the appropriate period. The right answers about available self-injectable adrenaline presentations were 40%. Conclusion: There were difficulty to recognize the maximum dose, self-injectable adrenaline dose and the correct time to repeat the adrenaline/medication, which increase the risk of overdose and adverse effects.